2015
DOI: 10.1016/j.jms.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Microwave measurements of cyclopropanecarboxylic acid and –OD isotopologue

Abstract: The microwave spectrum of cyclopropanecarboxylic acid has been measured in the 5-15 GHz region using a Flygare-Balle type, pulsed-beam Fourier-transform microwave spectrometer. These lower-frequency measurements are at a much higher resolution then the previous waveguide studies. The experimental rotational constants obtained in this study were A=7625.0432(17) MHz, B=2724.7672(8) MHz, and C=2382.0755(5) MHz. The centrifugal distortion constants determined were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To confirm that these splittings were indeed Doppler splittings, a 50/50 argon/neon mixture was used as the carrier gas and, as expected with the presence of argon, these Doppler splittings decreased slightly. In the study of the monomer of CPCA, there were no signs of splittings caused by internal rotation of the cyclopropane group 17,18,20 and the same seemed to hold true for the CPCA-FA dimer. Tunneling splittings were not observed, most likely because the dimer lacks the C 2vM symmetry, which may be necessary to create the symmetric double well potential with similar energies at the minima, allowing for the protons to tunnel through the energy barrier.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…To confirm that these splittings were indeed Doppler splittings, a 50/50 argon/neon mixture was used as the carrier gas and, as expected with the presence of argon, these Doppler splittings decreased slightly. In the study of the monomer of CPCA, there were no signs of splittings caused by internal rotation of the cyclopropane group 17,18,20 and the same seemed to hold true for the CPCA-FA dimer. Tunneling splittings were not observed, most likely because the dimer lacks the C 2vM symmetry, which may be necessary to create the symmetric double well potential with similar energies at the minima, allowing for the protons to tunnel through the energy barrier.…”
Section: Discussionmentioning
confidence: 77%
“…In the fit, the coordinates of all atoms for each monomer unit were held fixed to previously obtained structural values. 18,26 Following the results from the ab initio calculations, all atoms of formic acid had their z Cartesian coordinates fixed to the previously determined values. The z-coordinates were not set to be varied from these fixed positions from previous structural work.…”
Section: Molecular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of this nonlinear least-squares structure fit is 0.31 MHz. A Kraitchman analysis was also performed using the Kiesel KRA program on the low-energy CPCA monomer of all the measured 13 C substituted isotopologues and the previously measured parent and–OD isotopologues . The best-fit coordinates of the low-energy CPCA conformer are shown with the Kraitchman determined coordinates in Table .…”
Section: Molecular Structurementioning
confidence: 99%
“…They are important throughout biology and can be synthesized and utilized for many important reactions. , Structural information on these types of molecules is important to obtain to understand the chemistry and reactivity behind these enzymatic processes in biology or reactions performed in the lab. Infrared, Raman, microwave, and X-ray crystal structure studies have been reported previously for cyclopropanecarboxylic acid (CPCA). To obtain a more accurate gas-phase structure, transitions from 13 C singly substituted isotopologues were needed to continue from the previous work. This work extends the microwave spectroscopic work to include these 13 C measurements and allows us to obtain a best-fit gas-phase structure of CPCA.…”
Section: Introductionmentioning
confidence: 99%